UJI BEBERAPA DOSIS MINYAK SERAI WANGI (Cymbopogon nardus L.) SEBAGAI ATRAKTAN HAMA LALAT BUAH (Bactrocera spp.) PADA TANAMAN BELIMBING - Rustam, Rusli; Dewanti, Amanda (Universitas Islam Kadiri, 2024)
Starfruit (Averrhoa carambolae L.) is a horticultural plant having the main pest, the fruit fly Bactrocera sp. The solution is eviromentally friendly control is the use of trap combined with the attractant of lemongrass (Cymbopogon nardus L.). The purpose of this study is to get the dosage of lemongrass oil which is ablest to trap most fruit fly on starfruit plants. This research was conducted at BBI (Balai Benih Induk Hortikultura), Jl. Kaharudin Nasution, Pekanbaru and at Riau University Faculty of Agriculture Laboratory of Plant Pests, from Agustus to November in 2022. The treatment of the given dosage of lemongrass oil was 0 ml/trap, 0,25 ml/trap, 0,50 ml/trap, 0,75 ml/trap, and 1 ml/trap. The experiment used a complete randomized design with 5 treatments and 4 repetitions. The result showed that the species that attacks the starfruit plant is B. carambolae and B. umbrosa. The ablest dosage of lemongrass oil in trapping most fruit fly was 0,50 ml trap with an average population of 11,75 fruit flies for seven days.